Rancang Bangun Sistem Informasi Koperasi Simpan Pinjam Berbasis Website di Kantor Dinas Koperasi, Usaha Kecil dan Menengah, Perindustrian, dan Perdagangan Kabupaten Sumba Tengah - Siska Kahi Ninda; Adelbertus Umbu Janga; Alexander Adis (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of information technology has encouraged the transformation of the administrative system in various sectors, including savings and loan cooperatives. Cooperatives, MSMEs, Industry and Trade in Central Sumba Regency have been still managing savings and loan data manually using Microsoft Excel, which has an impact on service delays, the risk of recording errors, and low operational efficiency. This research aims to design and build a web-based savings and loan cooperative information system to improve the effectiveness of data management and service quality to members. The research method uses a software engineering approach through the stages of needs analysis, system design (use case diagram, interface design, and database), implementation with web technology, and system testing. The results of the study show that the developed system is able to accelerate the process of collecting member data, recording deposit and loan transactions, and preparing financial reports in an integrated manner. This system also makes it easier for members to access information and cooperative services online. Thus, the application of web-based information systems has been proven to improve the efficiency and accuracy of data management and the quality of cooperative services to its members.